Analysis of the Selection of Transportation Modes for College Trips - Ajie Setiawan; Firga Ariani; Agus Budi Purwantoro (Publikasi Indonesia, 2025)
The congestion conditions that occur on the UMY campus land and the route to the campus that has high density and congestion in the morning and evening, encourage the need for a study related to the reasons why students choose the mode of transportation used and the form of travel patterns that are carried out every day. The purpose of this study is to describe the demographic characteristics and characteristics of students' trips to college. The research method used was quantitative, with a cross-sectional design and purposive sampling techniques, and involved S1 and S2 students from the Faculty of Engineering. Data was collected through questionnaires, observations, and secondary sources, then analyzed using statistics. Based on the research results, most UMY students are 19-23 years old, male, earn above UMP, and have a Class C driver's license. Private cars are used stably over short-to-medium distances and dominate the high-cost category. Trans Jogja buses are popular for medium distances (8-14 km) among students on a budget. Online transportation is chosen for short-to-medium trips with higher costs. This study concludes that students prioritize flexibility, travel time efficiency, and affordability when selecting transportation modes. The policy implications show the need to improve public transportation access, provide campus shuttle services, and parking solutions to optimize student mobility and reduce congestion. Further research is suggested to explore policy frameworks for sustainable transportation in the campus environment.